Usaha Peningkatan Motivasi untuk Menciptakan Efektivitas Kerja pada Kejaksaan Tinggi Kalimantan Tengah: Efforts to Increase Motivation to Create Work Effectiveness in the Central Kalimantan High Prosecutor's Office - Megawati, Indah; Herawati, Dwiana (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2015)
Motivation is the driving force that creates enthusiasm for someone's work so that they will work together, work effectively and be integrated with all their efforts to achieve satisfaction. Motivation should be owned by someone so that they can easily achieve the expected work effectiveness. The purpose of this study is to get a clear picture of efforts to increase motivation to create work effectiveness in the Central Kalimantan High Prosecutor's Office in the City of Palangka Raya. The population of this study was all employees of the Central Kalimantan High Prosecutor's Office, amounting to 116 employees. The method used in this study is a quantitative method which is the opinion of the author or based on theories that are relevant to the problem with the Quantitative Data Technique, which is data obtained through numbers during a particular process. employee absenteeism, it can be concluded that the level of absenteeism of employees in 2015: 40.42%, in 2016: 45.29% and in 2017 the level of absenteeism of employees becomes 52.65%. Then the results of the data from the employee absentee level in 2015: 2.70%, 2016: 3.60% and in 2017 the employee absentee level becomes 5.45%. In the end, the success of efforts to increase motivation to create work effectiveness of employees at the Central Kalimantan High Prosecutor's Office in Palangka Raya, besides being determined by the Chairperson as well